The Effect Of Role Stress On Auditor Performance With Psychological Well-Being As Moderation Variables In BPKP Makassar - Fadhilah, Azisah; Alam, Syamsu; Tjan, Julianty Sidik (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Role stress is a condition where a person experiences pressure while carrying out his work, role pressure is generally associated with organizational conditions and with the place and position of individuals in the organization. This study aims to examine the Effect of Role Stress on Auditor Performance with Psychological Well-Being as a moderation variable at the Makassar City BPKP Office. The data in this study was obtained from the Auditors of the BPKP Makassar City Office who were willing to be respondents. This study used primary and secondary data by conducting direct research in the field by providing questionnaires / statement sheets to 36 respondents. Data analysis techniques are carried out by descriptive statistical analysis and PLS (Partial Least Square). The results showed that Role Stress had a negative and significant effect on Auditor Performance. Role Stress has a positive effect on Auditor Performance which is strengthened Psychological Well-Being as a Moderation Variable.